2015
DOI: 10.5152/turkpediatriars.2015.1411
|View full text |Cite
|
Sign up to set email alerts
|

Our patients followed up with a diagnosis of neurogenic pulmonary edema

Abstract: Neurogenic pulmonary edema is a clinical situation which developes as a result of central nervous system injury. It is rare in the childhood. Neurogenic pulmonary edema is a clinical diagnosis. Although the pathogenesis is not elucidated well, there is increase in pulmonary interstitial and alveolar fluid. The main principle in treatment of neurogenic pulmonary edema is supportive treatment and decreasing intracranial pressure as in acute respiratory distress syndrome. In this article, clinical properties of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…These changes are followed by the constriction of the pulmonary veins which lead to increase in pulmonary capillary hydrostatic pressure and later leading to damage of alveolar wall and leakage of fluid into the interstitium and intra-alveolar space along with hemorrhage resulting in the typical picture of neurogenic pulmonary edema. 1214 while Smith et al observed that in 7 out of 12 cases it is the increased pulmonary hydrostatic pressure which causes neurogenic pulmonary edema and not the increased lung capillary permeability. 15…”
Section: Discussionmentioning
confidence: 99%
“…These changes are followed by the constriction of the pulmonary veins which lead to increase in pulmonary capillary hydrostatic pressure and later leading to damage of alveolar wall and leakage of fluid into the interstitium and intra-alveolar space along with hemorrhage resulting in the typical picture of neurogenic pulmonary edema. 1214 while Smith et al observed that in 7 out of 12 cases it is the increased pulmonary hydrostatic pressure which causes neurogenic pulmonary edema and not the increased lung capillary permeability. 15…”
Section: Discussionmentioning
confidence: 99%
“…Neurogenic pulmonary oedema (NPE) is a form of respiratory distress that timewise correlates with an onset of acute brain injury and cannot be explained by either heart failure or fluid overload [101]. NPE can occur in several conditions, such as: subarachnoid haemorrhage (SAH), intracerebral haemorrhage, trauma brain injury (TBI), status epilepticus, subdural hematoma, epidural hematoma and other CNS acute states [102][103][104][105][106][107][108][109][110] All of the abovementioned diseases, despite different aetiologies, share some of the key elements for the development of NPE. Brain injuries that cause NPE are often expressed as an acute increase in the intracranial pressure (ICP), followed by decreased cerebral perfusion or a direct damage of brainstem and hypothalamus [111].…”
Section: Lungsmentioning
confidence: 99%
“…Neurogenic pulmonary oedema (NPE) is a form of respiratory distress that timewise correlates with an onset of acute brain injury and cannot be explained by either heart failure or fluid overload [ 101 ]. NPE can occur in several conditions, such as: subarachnoid haemorrhage (SAH), intracerebral haemorrhage, trauma brain injury (TBI), status epilepticus, subdural hematoma, epidural hematoma and other CNS acute states [ 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ]…”
Section: Lungsmentioning
confidence: 99%
“…These include enterovirus (EV)-71-induced brainstem encephalitis [20], subarachnoid bleeding (SAB) [21], intracerebral bleeding (ICB) [22], traumatic brain injury (TBI) [23], ischemic stroke [24], epilepsy [25], subdural hematoma [26], epidural hematoma [27], cerebral or spinal surgery [28], ce- rebral mass lesion [29], or other rarer causes (Table 1). According to a study of 36 patients with SAB-triggered NPE, predictors for the occurrence of NPE in patients with SAB were World Federation of Neurological Surgeons class, total power, and normalized low-frequency component [30].…”
Section: Types Of Triggers Of Npementioning
confidence: 99%